Vascular flora of a cerrado sensu stricto remnant in pratânia, state of São Paulo, southeastern Brazil - Carvalho, Marina Begali [UNESP]; Ishara, Katia Losano [UNESP]; Maimoni-Rodella, Rita C. S. [UNESP] (My University, 2010)
The Cerrado (Brazilian savanna) has suffered massive destruction in recent years, mainly due to the expansion of agricultural areas. Many remnants of this vegetation are still poorly studied. Therefore, the purpose of this study was to carry out a floristic survey in a remnant of Cerrado in the municipality of Pratânia, central-west region of state of São Paulo, southeastern Brazil. In total, 120 species (38 families, 88 genera) were registered. The families with greater richness were: Fabaceae (23 species), Asteraceae (15), Myrtaceae (10), Malpighiaceae and Rubiaceae (seven each) and Bignoniaceae (five). The shrub component was predominant in the study area representing 37.5% of the recorded species. A comparison among eight Cerrado areas showed greater similarity between areas with similar altitude. © 2010 Check List and Authors.
Keywords: Asteraceae; Bignoniaceae; Fabaceae; Malpighiaceae; Myrtaceae; Rubiaceae